Using Contouring Algorithms to Select Objects in the Robots’ Workspace - Yevsieiev, V.; Maksymova, S.; Demska, N. (Technical science research in Uzbekistan, 2024)
This paper explores the application of contouring algorithms to accurately highlight objects in the robots’ workspace. We present a mathematical description of the developed algorithm and a Python program that implements it in the PyCharm 2022.2.3 (Professional Edition) environment. Experiments carried out using this algorithm focused on outlining a matchbox while changing the pixel intensity threshold. The results obtained confirm the effective ness of the method and highlight its potential for optimizing the processes of robotic perception of the environment and interaction with objects.
Keywords: Industry 5.0; Сomputer Vision Systems